An Evaluation of the PRE-DELIRIC (PREdiction of DELIRium in ICu Patients) Delirium Prediction Model in Intensive Care Units in Türkiye - Samet Sayılan; Volkan Özen; Betül Tosun; Aylin Aydın Sayılan; Nurten Özen (Galenos Yayinevi, 2023)
Objective:This methodological study was conducted in order to carry out the adaptation and validation of the "PRE-DELIRIC score" prediction of delirium model in Türkiye among patients hospitalized in the intensive care unit (ICU).Materials and Methods:The research involved 172 patients treated in the intensive care units of a training and research hospital between October 2019 and April 2020. The study data were collected using (1) a data collection form to determine the participants' descriptive characteristics, (2) the PRE-DELIRIC score, and (3) the Confusion Assessment Method for the ICU (CAM-ICU). Receiver operating characteristic (ROC) analysis and diagnostic screening tests were applied for the purpose of determining cut-off points for the groups. The scores' sensitivity and specificity were calculated. Significance was evaluated at the p<0.05 level.Results:A statistically significant association was determined between the cut-off point obtained for the PRE-DELIRIC score (≥7.58%) and the study groups (p=0.003). Patients with PRE-DELIRIC scores of 7.58 or higher exhibited a 7.404-fold greater risk of being CAM-ICU-positive [odds ratio: 7.404; 95% confidence interval (CI): 1.638-33.469]. The area under the ROC curve was 64.9% (95% CI: 0.538-0.760), and the standard error was 5.6% (p=0.044).Conclusion:The PRE-DELIRIC score yielded reliable results in this study. It appears significant for patients with a likelihood of developing delirium within the ICU, and its use is recommended as a functional score that is easily applied and calculated.